1987
DOI: 10.1039/f19878303549
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance and electronic spectroscopy of low-spin manganese(II) complexes (C5R5)(CO)2(L)Mn with L = hydrazido(1-), arylamido, anionic nitrile and purine-type ligands

Abstract: The low-spin manganese(I1) oxidation state is stabilized in complexes (C,R,)(CO),(L)Mn, R = H, CH,, with the negatively charged and n-electron-rich nitrogen bases L = imidazolate, benzimidazolate, benzotriazolate, purinate, adeninate, 8-aza-adeninate, indolate, 4-pyridylamide, anilide, 4-tolylamide, p-phenylenediamide( 1 -), N,N-dimethyl-p-phenylenediamide( 1 -), 1,l -diphenylhydrazide( 1 -), dicyanamide, deprotonated malonodinitrile and t-butylmalonodinitrile. The paramagnetic compounds were obtained by syner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Spectra have also been reported for piano-stool Mn radicals in which one carbonyl has been replaced by a single-electron donor. These include MnCp*(CO) 2 L, L = SR, MnCp(CO) 2 (RNH), Mn(C 5 H 5− n Me n )(CO) 2 NR 2 , [MnCp(CO) 2 (4-cyanopyridine)] − , and MnCp(CO) 2 L′, L′ = RC 6 H 4 NH . In those cases, however, the complexes were shown to be essentially organic radicals stabilized by bonding to the MnCp(CO) 2 moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Spectra have also been reported for piano-stool Mn radicals in which one carbonyl has been replaced by a single-electron donor. These include MnCp*(CO) 2 L, L = SR, MnCp(CO) 2 (RNH), Mn(C 5 H 5− n Me n )(CO) 2 NR 2 , [MnCp(CO) 2 (4-cyanopyridine)] − , and MnCp(CO) 2 L′, L′ = RC 6 H 4 NH . In those cases, however, the complexes were shown to be essentially organic radicals stabilized by bonding to the MnCp(CO) 2 moiety.…”
Section: Resultsmentioning
confidence: 99%
“…Originally formulated as ( • ER n ) radical-containing organomanganese(I) species (with d 6 configuration implied), the EPR study showed a predominant Mn II (low-spin d 5 ) character with more conventional – ER n ligands. , Approaching the radical stabilization by using deprotonated p -phenylenediamine as the – ER n / • ER n redox-active ligand, it was possible, however, to achieve a rather balanced resonance situation () between both the Mn I / • ER n and Mn II / – ER n formulations . The 55 Mn hyperfine coupling was found at 4.24 mT, i.e., about two thirds the value for other low-spin Mn II species, whereas the 14 N coupling was correspondingly lowered to 0.65 mT from about 1.2 mT in genuine aminyl radicals …”
Section: “False” Metal Oxidation Statesmentioning
confidence: 99%
“…The ESR transition of the |±1 is not totally allowed between the |±1 levels and the |0 level. The g ∼ 2 values and the shape line for the transitions of Mn(III) ions are different from Fe(III) ESR signals with its g < 2 value, complement of other signals at low field [74,75]. A d 3 Mn(IV) ion in an octahedral symmetry has a ground state 4 A 2g and should show an isotropic resonance on its ESR spectrum with g < 2 value [76,77].…”
Section: Proton Nuclear Magnetic Resonancementioning
confidence: 99%